Light the Darkness : Story of the Hong Kong Red Cross, 1950-2000 - Lü, Dale (Book collections on Project MUSE., 2001)
These are two 'stories of Hong Kong' which have developed in tandem. Indeed, the 50-year history of the Hong Kong Red Cross in promoting humanitarian work is a fitting testimony to the successful nurturing of the society of Hong Kong and its citizens into loving and caring human beings.